A new species of the genus Polyodaspis Duda, 1933 (Diptera: Acalyptratae: Chloropidae) from Central Asia with a key to the Palaearctic species - Nartshuk, E.p. (Zootaxa, 2016)
A new species, Polyodaspis ferulae n. sp., from Central Asia (Uzbekistan) is described. The species was collected on inflorescences of Ferula foetida (Apiaceae). Siphonella levicola Becker in Becker and Stein, 1913 described from Iran is synonymized with Polyodaspis sulcicollis (Meigen, 1838) based on investigation of the holotype. A key to 9 species of the genus Polyodaspis Duda, 1933 is proposed with illustrations of male genitalia. Polyodaspis and Anacamptoneurum Becker, 1903 are treated as separate genera. New localities of P. sulcicollis (Meigen, 1838) from Kazakhstan and Central Asia are given.